Digital marketing utilization as a marketing medium for recycled waste craft products - Endah Ratna Arumi; Sufyan Ilham Adani; Abdul Rofiq Almuqorrobin; Yuka Rahmah Tiara Cahya; Atika Widiyati; Rizki Puji Astuti (Universitas Muhammadiyah Magelang, 2022)
Sugihmas Village is one of the villages in the Grabag District, Magelang Regency, which has a waste bank managed by youth organizations. Currently, the waste bank only functions as a garbage dump. The purpose of this service is to help manage waste into a more useful product, for example for crafts or something that has economic value, and the community is aware of the importance of environmental care. The methods used are socialization about waste and waste banks, making handicrafts from used materials, training and assistance on marketing using digital marketing, and monitoring and evaluation. The result of this activity is that the community has been able to process various types of waste into crafts that have a high selling value where the recycled products can be marketed through e-commerce applications as one of the uses of digital marketing. Thus, the recycled product can be recognized by many people and increase income.